How does terrorism affect the international trade of Muslims countries? - Ruiz Estrada, Mario Arturo; Park, Donghyun; Tahir, Muhammad; Khan, Alam (Springer Verlag, 2018)
In this paper, we propose a new model, namely the terrorism-trade and investment diversion simulator (TTID-Simulator). The simulator allows us to analyze the impact of terrorism on trade and investment diversion anywhere and anytime. Our central objective is to use the new model to evaluate the trade and investment diversion due to terrorism, and the ultimate effect on inflation rate, unemployment rate, and poverty rate. More specifically, we apply TTID-simulator to evaluate the economic effect of terrorism on Afghanistan, Iraq, Pakistan, and Syria, four countries which suffered a lot of terrorist activity in recent years. The focus of our analysis is trade and investment diversion, and our sample period runs from 1980 to 2016.